Study of the influence of soil composition on the yield and quality indicators of wheat grain (Texas Journal of Agriculture and Biological Sciences, 2022)
Winter grain is a highly profitable crop, the cultivation of which allows solving a number of issues and problems of agriculture and the national economy: defi-phytosanitary condition and soil structure, expansion of the composition of winter crop precursors, soil enrichment with organic matter